Environmental education focused on reuse of copper lithium-ion batteries in protein determination - Da Silva, Mayara Crepaldi [UNESP]; de Morais Chaves, Márcia Rodrigues; Monteiro Siqueira, Marcos Vinicius Bohrer; Antoniassi, Beatriz [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
The use of residues of electronic materials, such as lithium-ion batteries used in mobile phones, notebook computers, among others, is becoming more and more necessary. This is due to the accelerated growth of the use of these new technologies and, consequently, to the increase in the disposal of these components, which if done incorrectly ends up impacting the environment. The use of waste and prevention of pollution depend on actions of environmental education as a basis for the development of practical actions that result in the protection of the environment. However, there are few actions that involve environmental education within universities, in content and practical activities not related to the environmental area. In view of the above, this study proposed the development of a practical activity to be carried out in the discipline of Bromatology, through the use of copper slabs obtained from discarded lithium-ion batteries, in the preparation of the catalyst solution used in protein quantification by method of Kjeldhal. The objective was to demonstrate the feasibility of waste recovery associated with analytical techniques. In this way, the efficiency of the copper sulphate solution obtained from the copper slabs of the residual batteries was evaluated in the determination of the protein content in wheat flour. It was verified that the method using the reused copper of the batteries is very efficient, mainly for a didactic application, in which the focus is to make the student to learn a certain technique of analysis, not having, the necessity of a rigor in the obtained results. In this way, students were able to not only understand the content of the course but also to modify the method of analysis by reusing the waste batteries, thus becoming more aware and prepared citizens for the new forms of waste reuse.
Educação Ambiental Voltada para a Reutilização do Cobre de Baterias Íon-Lítio na Determinação de Proteínas
Keywords: Copper; Environmental Education; Higher Education; Kjeldahl Method; Reuse